2012
DOI: 10.1111/j.1600-0706.2012.20211.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the similarity of parasite communities in freshwater fishes using the phylogeny, ecology and proximity of hosts

Abstract: Parasite communities tend to be dissimilar in hosts that are geographically, phylogenetically, ecologically and developmentally distant from one another. The decay of community similarity is a powerful and increasingly common method of studying parasite beta diversity, but most studies have examined only a single type of distance. Here, we evaluate distances based on the phylogeny, ecology, spatial proximity and size of hosts, as predictors of the similarity of parasite communities in individual hosts, host po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 54 publications
4
54
1
Order By: Relevance
“…Species recovered were similar to those found in previous research on adult L. gibbosus in the St. Lawrence River (Locke et al, 2013), except that fewer adult trematodes were recovered. This is likely a result of using YOY hosts, as a juvenile's diet is not as diverse as an adult and so excludes transmission pathways present in older populations of L. gibbosus, and recruitment and maturation time is less (i.e.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Species recovered were similar to those found in previous research on adult L. gibbosus in the St. Lawrence River (Locke et al, 2013), except that fewer adult trematodes were recovered. This is likely a result of using YOY hosts, as a juvenile's diet is not as diverse as an adult and so excludes transmission pathways present in older populations of L. gibbosus, and recruitment and maturation time is less (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…and Diplostomum spp. have recently been demonstrated to contain cryptic species in the St. Lawrence River through DNA analysis (Locke et al, 2010(Locke et al, , 2013; as such, no attempt was made to identify individuals past genus to avoid improper identification. Species accumulation curves indicated that the majority of parasite taxa were likely accounted for by the analysis of ∼13 hosts (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) In some cases, only presence–absence data can be recorded, for example, when organisms grow clonally, are too abundant to count, or are difficult for nonexperts to identify taxonomically (Beisner, Peres‐Neto, Lindström, Barnett, & Longhi, 2006; Colwell, Chang, & Chang, 2004). (5) Presence–absence data are more appropriate than are abundance data for clarifying the effects of host characteristics on parasite similarity (Locke, Mclaughlin, & Marcogliese, 2013; Poulin, 2010; Poulin & Krasnov, 2010; Seifertová, Vyskočilová, Morand, & Šimková, 2008). We were not able to sample all of the leafminer species and their host plants within the short sampling period, but the use of presence–absence data may compensate for our sampling efforts.…”
Section: Methodsmentioning
confidence: 99%
“…Collapsed black clusters contain data (38 sequences, see Table 2) from metacercariae infecting sticklebacks in the present study and conspecifics from other studies. Genbank accessions are KM212028-65 (present study) and FJ477183-6; FJ477188-9; FJ477194-200; FJ477204-6; GQ292475-502; HM064610-47; HM064660-732; JF769450-2; JQ639170-95; JX986859-907; KC685359-60; KJ726433-507 Molecular data can clarify species boundaries and illuminate distributional patterns in fish parasite communities (Rellstab et al 2011;Behrmann-Godel 2013;Désilets et al 2013;Locke et al 2013), but unfortunately, we were unable to extend molecular species discriminations to all 12,077 metacercariae observed in the present study. However, under a null hypothesis that morphologically similar parasites observed in both lakes represent the same species, this is unlikely to have greatly affected overall patterns of inter-lake differences in parasite species composition.…”
Section: Discussionmentioning
confidence: 98%